Pupuk Organik Cair Berbasis Limbah Pisang Meningkatkan Kesuburan Tanah dan Ketersediaan Hara pada Budidaya Lada Perdu Secara Terapung - Nadhira Ghea Salsabila; Siti Masreah Bernas (Acta Solum, 2025)
Shrub pepper (Piper albi Linn) is a nutrient-demanding plant that requires additional fertilization to achieve optimal growth, especially in floating cultivation systems where nutrient availability is limited. Liquid organic fertilizer (LOF) derived from banana waste offers a sustainable alternative to enhance soil fertility and plant performance. This study aimed to evaluate the effects of banana-waste-based LOF on soil organic carbon, total nitrogen in soil and plant tissue, and the vegetative growth of shrub pepper (Piper albi Linn). The experiment was arranged in a randomized block design with two treatments: P0 (0 mL plant⁻¹) and P1 (50 mL plant⁻¹), applied weekly throughout the experimental period. The application of LOF significantly increased soil organic carbon and total nitrogen compared with the control. The P1 resulted in the highest soil organic carbon and nitrogen and enhanced nitrogen uptake. Furthermore, LOF application increased vegetative growth, particularly leaf number, indicating a positive response to increased nutrient availability. In conclusion, banana-waste-based LOF efficiently provides essential nutrients and improves soil fertility in floating cultivation systems. The findings highlight its potential as an environmentally friendly soil amendment to support sustainable production of shrub pepper (Piper albi Linn) and reduce reliance on chemical fertilizers.